2019
DOI: 10.9734/jalsi/2019/v20i130076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phyllanthus amarus on Some Reproductive Indices of Male Albino Rats

Abstract: Background: Medicinal plants have been a good source of drugs for humans, but chronic and prolong use of medicinal plants like Phyllanthus amarus for the treatment of malaria and other disorders are issues of concerns. This study evaluated the effect of Phyllanthus amarus on reproductive organs and sperm parameters in albino rats. Materials and Methods: Twenty-four healthy male albino rats of 12 weeks old were assigned into four groups with six rats in each group using a Completely Randomized Design (CRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This result agrees with work of [18] who observed that the methanol extracts of Phyllanthus amarus (800 mg/kg) caused an insignificant change in the levels of Luteinizing (LH) and Follicle stimulating (FSH) hormone. [19] in the study of the effect of Phyllanthus amarus on some reproductive indices of male albino rats observed reduction in weight of testes and epididymes, sperm motility, sperm viability, sperm count and sperm head abnormalities in male rats treated with Phyllanthus amarus when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with work of [18] who observed that the methanol extracts of Phyllanthus amarus (800 mg/kg) caused an insignificant change in the levels of Luteinizing (LH) and Follicle stimulating (FSH) hormone. [19] in the study of the effect of Phyllanthus amarus on some reproductive indices of male albino rats observed reduction in weight of testes and epididymes, sperm motility, sperm viability, sperm count and sperm head abnormalities in male rats treated with Phyllanthus amarus when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…2 Phyllanthus amarus is a small erect herbal plant that grows upto 10-50 cm and it has small leaves, its stem have green capsules with flowers and very small fruits that burst open when dry. This plant is commonly called stonebreaker 3 .Phyllanthus amarus is used in traditional medicine for gastrointestinal, kidney, liver, menorrhagia and other conditions. 4 Indian traditional systems of medicine like Siddha and Ayurveda have suggested to increase the body's natural resistance to disease under the concept of 'Rasayana'.…”
Section: Introductionmentioning
confidence: 99%